The Anglo-Scottish border and the shaping of identity, 1300-1600 - Bruce, Mark Paul; Terrell, Katherine H. (New Middle Ages., 2012)
"Theorizing the Borders: Scotland and the Shaping of Identity in Medieval Britain explores the roles that Scotland and England play in one another's imaginations. This collection of essays brings together eminent scholars and emerging voices from the frequently divergent fields of English and Scottish medieval studies to address such questions as: How do subjects on both sides of the Anglo-Scottish border define themselves in relation to one another? In what ways do they influence each other's sense of historical, cultural, and national identity? What stories do they tell about one another, and to what ends? How does the shifting political balance--as well as the shifting border--between the two kingdoms complicate notions of Scottishness and Englishness? What happens to important texts, genres, and even poetic forms when they cross this border? How do texts produced in the Anglo-Scottish borderlands transform mainstream notions of Scottish and English identities?"--